Autonomie und Verantwortung in digitalen Kulturen Privatheit im Geflecht von Recht, Medien und Gesellschaft - Berger, Franz X.; Deremetz, Anne; Hennig, Martin; Michel, Alix (Philosophische Praxis, 2021)
The increasing complexity of networked systems casts doubt on the self-determination in the digital sphere. Externally predetermined algorithms and practices of third-party data processing raise questions as to the protection of and the danger to autonomy and the freedom of expression. At the same time, the legal, political, ethical, social, and economic responsibility for the consequences of digital transformation processes for societies, collectives, and individuals remains undetermined. Precisely in this field, the present interdisciplinary volume would like to stimulate a discussion on responsibilities and impact assessments; in which regard, it researches problems in digital cultures, tackles possible solutions, and discusses conflicts of economic, political, and social systems. With contributions by Anna K. Bernzen, Barbara Büttner & Carsten Ochs, Stephan Dreyer, Hans-Christian Gräfe & Andrea Hamm, Hermann Jakobi & Elizaveta Saponchik, Thomas Krämer-Badoni & Jens Crueger, Wulf Loh, Tim Raupach & Phillip Siedenburg, Caroline Richter & Christian Lenk, Alexander Schiff, Julia Schröder, Lea Watzinger and Florian Wittner